2021
DOI: 10.1055/s-0040-1717083
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Fibrin Enhances Surgical Wound Healing in Total Laryngectomy

Abstract: Autologous growth factor (AGF) is a cytokine that has gained medical research interest because it helps improve and accelerate the wound healing process. Platelet-rich fibrin (PRF) is the latest generation of platelet concentrate that can be obtained through a simple procedure known as AGF referencing. One of the most common complications of total laryngectomy (TL) is pharyngocutaneous fistula. To prevent this complication, health care providers must closely monitor the postoperative wound healing process.This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…28,36 Platelet concentrates offer not only wound healing and tissue regeneration benefits but also aid in pain reduction and infection prevention during treatment. 13,37 However, the precise mechanism of action of growth factors within APCs in different wound types and stages of wound healing remains unclear. Furthermore, the influence of platelet activation and potential adverse reactions associated with the preparation of certain APCs products require further elucidation, along with the establishment of standardized preparation protocols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,36 Platelet concentrates offer not only wound healing and tissue regeneration benefits but also aid in pain reduction and infection prevention during treatment. 13,37 However, the precise mechanism of action of growth factors within APCs in different wound types and stages of wound healing remains unclear. Furthermore, the influence of platelet activation and potential adverse reactions associated with the preparation of certain APCs products require further elucidation, along with the establishment of standardized preparation protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet concentrates offer not only wound healing and tissue regeneration benefits but also aid in pain reduction and infection prevention during treatment 13,37 . However, the precise mechanism of action of growth factors within APCs in different wound types and stages of wound healing remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…63 The benefit of using autologous PRP to improve wound healing in acute wounds is more controversial but favors reduced risk of infections. 64 Additionally, promising future applications in otolaryngology for autologous PRP include enhanced wound healing following total laryngectomy, 65 improved vocal quality in treatment of vocal fold scar and atrophy, 66,67 and improved healing of chronic tympanic membrane perforations following tympanoplasty. 68,69 Hair Follicle Transplantation Brown and McDowell were the first to observe that wounds in areas without hair follicles, such as the palms and soles, heal slower than wounds in hair-bearing areas and proposed that hair follicles play a role in wound healing.…”
Section: Platelet-rich Plasmamentioning
confidence: 99%
“…Various treatment modalities, materials, and drugs have been introduced to facilitate laryngeal cartilaginous healing and prevent complications. Several clinical and experimental studies have shown different degrees of success and limitations of these treatment modalities, such as the use of amniotic membrane (AM), 2 adipose‐derived stem cells (ASCs), 3 seeded scaffolds, 4 and platelet‐rich plasma (PRP) 5 in laryngeal defects repair.…”
Section: Introductionmentioning
confidence: 99%
“…as the use of amniotic membrane (AM), 2 adipose-derived stem cells (ASCs), 3 seeded scaffolds, 4 and platelet-rich plasma (PRP) 5 in laryngeal defects repair.…”
mentioning
confidence: 99%